Does inducing choice procedures make individuals better off? An experimental study - Mittone, Luigi; Papi, Mauro (Theory and decision, 2017)
Over the years the psychological and economic literature on multi-attribute individual decision-making has focused its attention on examining what class of heuristics better describes subjects’ behaviour. In contrast, motivated by the proliferation of online choice platforms, we investigate whether inducing subjects to use holistic vs. characteristic-based search (CBS) procedures has an effect on the quality of their decision by proposing a between-subject experiment involving an innovative visual choice task. We find that encouraging subjects to use CBS heuristics as opposed to holistic ones makes them better off. We also examine how subjects’ performance is related with complexity, time pressure, and random choice by running simulations and link our results to the related literature.